Pembentukan Karakter Qur’an Sejak Usia Dini Perspektif Hamka: Studi Pengaruh Hafalan Al-Qur’an bagi Anak Usia Dini di Sekolah Suturuzzhulam - Siregar, Anita Putri; Munandar, Munandar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the effect of Qur’an memorization on the formation of Qur’anic character in early childhood at Suturuzzhulam School, Tembung, from Buya Hamka’s perspective. Using a quantitative Pre-Experimental One-Group Pretest-Posttest design, data were collected from 20 first-grade students selected through saturated sampling via questionnaires, observation, and documentation, then analyzed with descriptive statistics and a paired sample t-test. Results show a significant increase in memorization scores, from a pretest mean of 11.35 to a posttest mean of 70.35 (t = 6.83 > t table 2.093, α = 0.05), with 13 of 20 students completing Juz 30. The tahfiz program also fostered religious, disciplined, responsible, patient, and respectful character traits, though character development was significantly higher at school (49.0%) than at home (40.0%) (t = 2.78). These findings support Buya Hamka’s view that Qur’anic character formation must begin early through instilling tauhid and sustained habituation, indicating that parental involvement at home needs to be strengthened.